الاقتصاد اللغوي في مواقع التواصل الاجتماعي ودوره في إنجاح العملية التواصلية - مداني، إيمان Madani, Iman; عيصام، حسيني صفوان Eissam, Hosseini Safwan (جامعة الأمير عبد القادر للعلوم الإسلامية, 2019)
إن ما يقصده المرء في سياق اتصاله اليومي بالآخرين من مفردات، ومقاطع، وأصوات يدخل في باب الفائض، ولا يعتبر ضروريا لكي يبلغ المرسل رسالته إلى التلقي بشكل سليم، فيعمد في أغلب رسائله على مبدأ الاقتصاد الذي يعني اقتصار اللغة على العدد الأدنى من القواعد، والمصطلحات، والرموز، والفونيمات وبالأحرى هو ميل اللغة إلى توفير الجهد عن طريق الاختصار، والحذف، والاختزال. ونحن في هذا المقال العلمي سنحاول الوقوف على حد الاقتصاد اللغوي عند اللغويين العرب القدامى والمحدثين، وكذا اللسانيين الغربيين معرجين على رمزية الممارسات اللغوية لدى مستخدمي مواقع التواصل الاجتماعي. وفي الشق التطبيقي للدراسة ركزنا على حضور هذا المبدأ اللساني-الاقتصاد اللغوي-وأهم تمظهراته في مواقع التواصل الاجتماعي، وأثره في إنجاح العملية التواصلية. وأنهينا الدراسة بجملة من النتائج.
Most of what a language user means in the context of his daily use by his words, sequences and sounds can be included in the surplus section, and most of it is not that necessary for him to communicate his message to the recipient. In most of his letters he uses the principle of "economy", which means that the language is limited to the minimum number of rules, Symbols, and phonemes, or in other words is a language tendency to provide effort by abbreviation, deletion and reduction. In this scientific article, we will try to talk about the concept of "linguistic economy" among the classical and modern Arabic linguists, as well as the Western linguists too, who are introduced to the symbolic language practices of users of social networking sites. In the applied part of the study we focused on the presence of this concept in it's manifestation in social networking sites and its impact on the success of the communication process. The study ended with a series of results
Keywords: علم الاجتماع اللغوي -- التواصل الاجتماعي -- الاقتصاد اللغوي